2018
DOI: 10.1111/1747-0080.12462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of a nutrition assistant role in a head and neck cancer clinic

Abstract: The nutrition assistant role resulted in improved patient satisfaction and maintenance of nutritional outcomes demonstrating the effectiveness of this role in supporting the management of head and neck cancer patients within a multidisciplinary treatment clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The other five abstracts described the evaluation of the effectiveness of new nutrition-related clinical processes, pathways, models of care, and/or roles [42][43][44][45][46]. One conference abstract and the one article evaluated the benefit of training a nutrition assistant to perform nutrition screening and intervention for oncology patients and found that the role of nutrition assistants could benefit patient outcomes [42,46]. Further information about the seven abstracts is summarized in Table 5.…”
Section: Review Of Malnutrition and Nutrition-focused Qips In Cancer mentioning
confidence: 99%
“…The other five abstracts described the evaluation of the effectiveness of new nutrition-related clinical processes, pathways, models of care, and/or roles [42][43][44][45][46]. One conference abstract and the one article evaluated the benefit of training a nutrition assistant to perform nutrition screening and intervention for oncology patients and found that the role of nutrition assistants could benefit patient outcomes [42,46]. Further information about the seven abstracts is summarized in Table 5.…”
Section: Review Of Malnutrition and Nutrition-focused Qips In Cancer mentioning
confidence: 99%
“…Both the biopsy process and the treatment of HNC suffers, which includes radiation, surgery, and chemotherapy, have adverse influences on patients’ health related quality of life [ 17 ]. Distortions of voice, taste, chewing, swallowing, hearing, and breathing may produce psychological burden for decades after the end of the treatment course [ 18 ]. Critical weight loss (5%) during treatment was observed to affect 66% of patients with HNC [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 , 25 ] These initiatives have encouraged expansion of AHAs’ scope of practice and greater utilisation of AHAs by professions other than physiotherapy and occupational therapy. [ 26 , 27 ] Our findings potentially reflect that AHAs working in the Victorian public healthcare setting are well supported to undertake a predominantly patient-facing role.…”
Section: Discussionmentioning
confidence: 81%